PENILAIAN KINERJA KEUANGAN DENGAN PENDEKATAN ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tante Meylan A.J Kaba; Hironnymus Jati; Wehelmina Ndoen (Journal of Management Small and Medium Enterprises (SMEs), 2018)
This research method is quantitative with descriptive approach. The result of this study indicatesthat state-owned banks listed on the Indonesia Stock Exchange has an EVA value smaller than 0 ornegative value pads in 2013 and 2015 which amounted to Rp. (20.167.583,35) and Rp.(6.414.905,00). This position means there is no process of adding economic value to the company, inthe sense that the profit generated by the company is unable to meet the expectations of creditors andshareholders. A bank listed on the Indonesian Stock Exchange with a negative in 2016 of Rp.(8.080.262). A negative MVA explains that the company has poor financial performance from theexternal side, which has failed to add value to capital entrusted by investors to the company, becausethe company has a small stock market place.Keywords : Economic Value Added, Finance Perfomance, Market Value Added